Using Word Wall In Teaching English Vocabulary And Its Impact On The Students’ Vocabulary Achievement - Stefani Marcanidya Philippus; Wahju Bandjarjani (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
In. This study aims to determine students' perceptions of the use of video dubbing techniques in teaching students speaking skills in English by. This research was conducted to prove that using the video dubbing technique can improve the speaking ability of class X students from a private high school in Surabaya. The research method used qualitative case study. The participants of this study were students of class X at a private high school in Surabaya.Consisted of 5 students who had the most relevant answers. Data collection was carried out by means of structured interviews in witch questions were asked in the order that had been prepared.The results of this study indicated that students' perceptions of using video dubbing media were generally positive. Students agree that learning to speak using Video Dubbing could help them improve their speaking skills. Apart from that, learning through Dubbing videos has also fun and interesting.